1996
DOI: 10.1243/pime_proc_1996_210_421_02
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral Disc Response to Cyclic Loading—An Animal Model

Abstract: The viscoelastic response of a lumbar motion segment loaded in cyclic compression was studied in an in vivo porcine model (N = 7). Using surgical techniques, a miniaturized servohydraulic exciter was attached to the L2-L3 motion segment via pedicle fixation. A dynamic loading scheme was implemented, which consisted of one hour of sinusoidal vibration at 5 Hz, 50 N peak load, followed by one hour of restitution at zero load and one hour of sinusoidal vibration at 5 Hz, 100 N peak load. The force and displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Disc stiffness and relaxation levels were previously reported to return to pre-loaded levels after 18 h of recovery yet disc height before and after loading was not measured (Johannessen et al, 2004). Nonrecoverable deformations were previously reported in a porcine model under cyclic loading (Ekstrom et al, 1996), and non-recoverable deformations in cartilage were also reported under strains as low as 2% (Langelier and Buschmann, 2003) consistent with our findings. Nonrecoverable deformations in motion segments are consistent with the hypothesis that minor damage to vertebral bodies can lead to progressive disruption of the adjacent discs (Adams et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Disc stiffness and relaxation levels were previously reported to return to pre-loaded levels after 18 h of recovery yet disc height before and after loading was not measured (Johannessen et al, 2004). Nonrecoverable deformations were previously reported in a porcine model under cyclic loading (Ekstrom et al, 1996), and non-recoverable deformations in cartilage were also reported under strains as low as 2% (Langelier and Buschmann, 2003) consistent with our findings. Nonrecoverable deformations in motion segments are consistent with the hypothesis that minor damage to vertebral bodies can lead to progressive disruption of the adjacent discs (Adams et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Not only did the spines fail to recover during an unloading period equal in length to the loading period, 8,21 most still had not completely recovered in unloaded periods double or more the length of time of loading. Gedalia et al observed that the lumbar structures failed to recover after more than double the amount of time allotted for creep testing.…”
Section: Discussionmentioning
confidence: 99%
“…21 Likewise, Eckstrom et al induced creep in the porcine spine over 1 h, and observed its recovery for an hour following the removal of load. 8 Gedalia et al performed similar testing in lumbar structures, loading them for 50 min and monitoring recovery after 50 min. 10 Finally, Solomonow et al subjected cat spines to cyclic loading for 50 min, and observed the recovery for 7 h. 32 Interestingly, each of these studies found that the recovery of creep in the spine requires more time than the duration over which the load was applied.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment set-up can explain different values in comparison to other dynamic studies [11,23], as well as the preparation of the specimens and the choice of the viscoelastic model [6].…”
Section: Resonant Frequencymentioning
confidence: 99%
“…To achieve these models, it is necessary to know the mechanical properties of the different structures of the human body, and we have focused first on the intervertebral disc. Most studies of the dynamic behaviour of the intervertebral disc have focused on the physiological loading of daily life and have considered creep [13], cyclic loading [2, 6,14,15,16,17], fatigue with a frequency around 1 Hz [1,19] or impact tests [22]. The goal of this study is to characterise the dynamic stiffness and damping of human intervertebral discs subjected to vibration from 5 to 30 Hz in a sitting position in a car.…”
Section: Introductionmentioning
confidence: 99%